A mixed‐methods evaluation of a Recovery College in South East Essex for people with mental health difficulties. (3rd June 2019) - Wilson, Ceri; King, Matthew; Russell, Jessica
Abstract: Recovery Colleges aim to assist people with mental health difficulties in the journey to recovery through education. They bring together professional and lived experience of mental health challenges in a non‐stigmatising college environment and operate on college principles. All courses are designed to contribute towards well‐being and recovery. Despite the ever‐growing number of Recovery Colleges (both in the UK and internationally), the evaluative evidence is limited; comprising mostly non‐peer‐reviewed evaluations, audits and case studies. The present article comprises a mixed‐methods evaluation of a newly established Recovery College in South East Essex, UK. The evaluation comprised questionnaires of mental well‐being and social inclusion at baseline and 3 and 6 month follow‐up, in addition to three focus groups. There were significant improvements in both mental well‐being and social inclusion from baseline to 6 month follow‐up (25 participants completed the measure of well‐being at both time points and 19 completed the measure of social inclusion). This was supported by additional free‐text questionnaire comments and focus group findings (17 participants participated across the focus groups), with reports of increased confidence, reduced anxiety and increased social inclusion/reduced social isolation. Additionally, at 6 month follow‐up a majority of respondents were planning on attending courses external to the Recovery College, volunteering and/or gaining paid employment. Challenges and recommendations identified through the focus groups indicate the importance for standardisation of processes (which is particularly important when multiple organisations are involved in the running of a Recovery College), as well as consideration of longer‐running courses. Funders should continue to invest in the Recovery College movement as the growing evidence‐base is demonstrating how these colleges can help address the high prevalence of mental health difficulties, by promoting mental well‐being and social inclusion.